UNKNOWN DEAD BODIES PROFILE AND PATTERN OF CAUSE OF DEATH IN CENTRAL INDIA-ONE YEAR RETROSPECTIVE AUTOPSY BASED STUDY IN INDORE, MADHYA PRADESH (Journal of Forensic Medicine & Toxicology, 2019)
Unknown dead bodies are those dead bodies in which identity not determined till the examination and reporting. Unknown dead body brought for medico legal autopsy is significant proportion of total medico legal autopsy conducted. To determine identity along with cause of death in unknown cases mostly brought by police without any reliable history is laborious work. We have done study in relation to both profile and cause of death in unknown dead bodies. Out of total 2195 dead bodies brought for medico legal autopsy in one year (2015), we conducted 226 (10.30%) unknown dead bodies examination in which 186 cases (82.30%) were male, female cases numbered 33 (14.60%) and in 07 (3.10%) cases sex could not be determined. Maximum number of 52 (23.01%) cases seen in age group 41-50 years seen, out of which 44 (19.41) were male and 08 (3.54) cases were female. Followed by age group 31-40 years in which 46(20.35%) cases seen out of which 40 (17.70%) were male and 06 (2.65%) were female. Seasonal variation seen in our study, maximum cases in summer 81 (35.85%) followed by monsoon season 91 (40.27%), and least in winter season 56 (24.78%). Distribution of cases according to cause of death in unnatural death showed maximum number cases .
Keywords: Unknown; Mortuary; Autopsy; Seasonal variation; Injuries; Asphyxia; Pathology; Poisoning